Strategies of conditional cash transfers and the tactics of resistance. (February 2017) - Garmany, Jeff
This article examines how poor people negotiate obligations placed on them by social welfare initiatives. More specifically, it considers conditional cash transfer programs (CCTs), and the ways beneficiaries harness program conditionalities to make demands on authorities, in some cases even enacting subtle forms of resistance to state governance. Drawing from Michel de Certeau, it argues that while CCT conditionalities function as strategies of state development, they are not always/already under exclusive state control. Marginalized groups like CCT recipients can tactically harness these conditionalities. Through such tactics, poor people make demands on the state and deflect program obligations, but in calculated ways that avoid exposing them to greater vulnerability. Drawing from empirical data collected as part of a case study in rural northeastern Brazil, this article contributes to existent bodies of literature on CCTs, governance, and critical development studies in the 21st century.